One asset does not fit all: Inflation hedging by index and horizon - Stefania D'Amico; Thomas B. King (Federal Reserve Bank of Chicago, 2023)
We examine the inflation-hedging properties of various financial assets and portfolios by estimating simple time-series models of the joint dynamics of each asset-inflation pair, for multiple inflation indices and at horizons from one month to 30 years. There is no one-size-fits-all approach to inflation hedging: the optimal hedge depends on the particular types of prices that an investor is exposed to and at which horizons. For example, food and energy prices are easy to hedge with commodities and certain stock portfolios, while non-housing service prices and wages are not highly correlated with any financial asset. Inflation-protected bonds are good hedges for headline consumer inflation at horizons matching their maturities but can perform quite poorly at shorter horizons and for other price indices. During the inflationary period of 2020 - 2022, many historical hedging relationships failed, as monetary policy tightening lagged inflation.
Keywords: 330; Inflation; real assets; Treasury Inflation Protected Securities; hedging